Polysomnographic titration of non-invasive ventilation in motor neurone disease (3TLA): study protocol for a randomised controlled trial - David J. Berlowitz; Dominic Rowe; Mark E. Howard; Amanda Piper; Marnie Graco; Sabine Braat; Bhajan Singh; Tanara Viera Souza; Natasha Lannin; Alistair McLean; Abbey Sawyer; Kate A. Carey; et al. (Trials)
Abstract Background Non-invasive ventilation (NIV) uses positive pressure to assist people with respiratory muscle weakness or severe respiratory compromise to breathe. Most people use this treatment during sleep when breathing is most susceptible to instability. The benefits of using NIV in motor neurone disease (MND) are well-established. However, uptake and usage are low (~ 19%) and there is no consensus on how to best implement NIV in MND in Australia. Consequently, clinical practice models are highly variable. Our team has recently provided evidence that specific and individualised NIV titration using a sleep study (polysomnography; PSG) leads to better outcomes in people with MND. However, for this clinical practice model to result in sustained benefits, evidence of effectiveness across multiple sites, as well as culture and practice change, must occur. Methods A two-arm, assessor-blinded, individual participant randomised controlled trial in MND care centres across Australia will be undertaken. Two-hundred and forty-four participants will be randomised (1:1) to either the intervention group (PSG-assisted commencement of NIV settings; PSG) or a control group (sham PSG). Participants will be asked to use their NIV device for 7 weeks and will then return for follow-up assessments. Respiratory, sleep and patient-reported outcome measures will be collected at baseline and follow-up. The primary aim is to determine if the proportion of participants using NIV for > 4 h/day during the intervention period is higher in the PSG than the control group. A process evaluation, health economic evaluation and 12-month cohort follow-up will be undertaken and reported separately. Discussion The results of this trial will demonstrate the effects of PSG-assisted titration of NIV on usage of NIV in people with MND. We hypothesise that the PSG intervention will improve synchrony between the user and the machine, which will lead to greater NIV usage compared to the control group. Trial registration ClinicalTrials.gov NCT05136222. Registered on November 25, 2021.